Answer:
Q3: A
Q4: 9x² + (-x) + (-3)
Step-by-step explanation:
Q3: C (63) => x = 63. => C(x) = 36 x 63
Q4: f(x) + g(x) = 7x² - 5x + 3 + 2x² + 4x - 6 = (7x² + 2x²) + (-5x + 4x) + (3 - 6) = 9x² + (-x) + (-3)
Answer:
A TRUE B FALSE C FALSE
Step-by-step explanation:
I believe this is a function. I am not sure because one of the pairs only has a y value.
But the rule is there can only be one x value for one y value so for example, you can have (3.7) and (3,9) and the same for the y values.
Simplest Form: ![7 : 2](https://tex.z-dn.net/?f=7%20%3A%202)
How to Simplify a Ratio A : B when A and B are both whole numbers:
- List the factors of A
- List the factors of B
- Find the greatest common factor of A and B, GCF(A, B)
- Divide A and B each by the GCF
- Use the whole number results to rewrite the ratio in simplest form
Try to reduce the ratio further with the greatest common factor (GCF).
<em>The GCF of 14 and 4 is 2</em>
Divide both terms by the GCF, 2:
14 ÷ 2 = 7
4 ÷ 2 = 2
The ratio 14 : 4 can be reduced to lowest terms by dividing both terms by the GCF = 2 :
14 : 4 = 7 : 2
Therefore:
14 : 4 = 7 : 2
I Belive it might be ballad